Effect of Bovine Serum Albumin (BSA) Concentration on Cryopreservation of Booroolong Frog Sperm with Evaluation of Post-Thaw Motility in Caffeine - Zara M. Anastas; Aimee J. Silla; Phillip G. Byrne; Rebecca J. Hobbs; Michael S. McFadden; Jonathan Daly; Justine K. O’Brien (Veterinary Sciences)
Reproductive technologies, including sperm cryopreservation, offer conservationists enhanced capacity to genetically manage populations and improve the outcomes of conservation breeding programs (CBPs). Despite this potential, the post-thaw quality of amphibian sperm is highly variable following cryopreservation, and research focused on protocol refinement is needed. The aim of this study was twofold: (1) to investigate the effect of the addition of bovine serum albumin (BSA) to the cryopreservation medium (pre-freeze), and (2) the effect of the addition of caffeine to the activation medium (post-thaw), on post-thaw sperm characteristics in the critically endangered Booroolong frog (Litoria booroolongensis). Spermic urine samples were collected from 14 male frogs following hormonal induction of spermiation, and each sample was split among three cryopreservation treatments, where the cryopreservation medium contained either 0 (control), 0.5, or 1% BSA (w/v). Samples were cryopreserved and thawed, and sperm motility was then activated in one of two activation treatments: Milli-Q water (control) or Milli-Q water plus 4.5 mM caffeine. Sperm viability (proportion live/dead) was assessed using fluorescent microscopy, and sperm motility metrics were evaluated using computer-assisted sperm analysis (CASA). Results from this study showed that BSA concentration had no effect on post-thaw sperm viability. Additionally, neither BSA concentration nor activation in caffeine influenced post-thaw sperm motility characteristics (total motility, forward progressive motility, and velocity). Assessment time of sperm motility varied from 5 to 13 min post-activation and was significantly correlated with each motility measure, with motility and velocity metrics decreasing as time post-activation increased. The results reported herein provide no evidence for an effect of BSA or caffeine at the concentrations tested on post-thaw sperm characteristics in the Booroolong frog, but they highlight the time-sensitive nature of sperm assessment post-thaw and implications for the timing of sperm handling during assisted fertilisation efforts.